(untitled) (College of Basic Education Research Journal, 2025)
Current research dealt with Jews of Badinan by shedding light on their population, residence clusters in cities and villages of the region, in addition to their economic, social and cultural conditions during monarchy, Origins of this community go back to Jews who were captured by Assyrian kings during their campaigns on Palestine. Jews worked in agriculture animal husbandry, trade as well as being goldsmiths, weavers, tanners, etc. As for their social life, they had special laws, regulations, customs and traditions, their temples spread in cities and some villages, not to forget to mention selected persons of Jewish community to conduct their religious and worldly affairs. Jews had their own schools in region that taught Students basics of Jewish religion.